TRANSFORMASI BADAN KREDIT DESA MENJADI LEMBAGA KEUANGAN MIKRO PERSPEKTIF HUKUM EKONOMI SYARIAH - Fuad, A. Zaky; Asmawi, Asmawi; Aibak, Kutbuddin (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2022)
This research is motivated by the rise of the Financial Services Authority Regulation (POJK) 10/POJK.03/2016 concerning the Fulfillment of Provisions for Rural Banks and the Transformation of Village Credit Boards Given Status as Rural Banks, which this regulation requires BKD to make an action plan (action plan) and carry out the process of transformation into a financial institution that is legal and recognized by law. The focus and questions in this research are: (1) the transformation of BKD into an MFI before POJK Number 10 of 2016?; (2) transformation of BKD into MFI after POJK Number 10 of 2016?; and (3) transformation of BKD into MFI in the perspective of sharia economic law? This research employs empirical legal research with a sociological juridical approach, a conceptual approach, and a statutory approach. Data collection was carried out by participant observation, in-depth interviews with BUMDES in Genteng District and several related parties and documentation methods, then analysed using deduction, induction and comparative analysis. The results showed that the Bumdes Lembu Suro Genteng Kulon did not join the Bumdes Bersama, the Bumdes Lumbung Makmur Genteng Wetan joined the Bumdes Bersama and the Bumdes Rukun Makmur Kembiritan did not join the Bumdes Bersama. These three Bumdes have implemented the “Three New Pillars” initiated by William Richard Scott with three indicators, namely: regulatory, normative and cultural-cognitive. Each indicator has the following aspects of view: (1) the basis of compliance, (2) the basis of the rules, (3) the implementation mechanism, (4) the logic of sanctions, (5) the indicators for the consideration of sanctions, (6) the impact of the determination of sanctions, and (7) basis for determining legitimacy. Bumdes Lembu Suro Genteng Kulon in the